Diffusion in solids--past, present and future : proceedings of the International Conference on Diffusion in Solids--Past, Present and Future, held in Moscow, Russia, May 23-27, 2005 - Bokshteĭn, B. S. (Boris Samuilovich); Straumal, B. B. (Boris B.) (Diffusion and defect data. Defect and diffusion forum ;, 2006)
The topic of diffusion science becomes more and more important: this collection of timely papers is divided into seven chapters. The first three are dedicated to macroscopic and microscopic theories of diffusion. Chapter 4 is dedicated to diffusion in nanomaterials, while chapter 5 is devoted to the topic of diffusion along grain and interphase boundaries. This second topic is, of course, not new: it has been discussed for many years, but new themes have evolved in recent times in connection with segregation and stress effects upon grain-boundary diffusion. Both effects become more and more influential in the case of nanomaterials. This is because the fraction of intercrystalline boundaries, and the magnitudes of property gradients (including stress) attain critical values; due to the small sizes of the grains and particles. Chapter 6 deals with grain-boundary phase transitions; especially wetting and liquid penetration. This topic is attracting increased attention both because of its numerous applications and because it offers the opportunity to take a fresh look at the problems of non-equilibrium boundaries and the thermodynamics and kinetics of phase transitions in non-equilibrium systems. One of the hottest topics is the transition from diffusion based upon random walks (in systems close to equilibrium) to directed flows of interface penetration processes (when far from equilibrium). Finally, in chapter 6, the problems of new materials design are discussed, with diffusion as an aid to their testing. This volume will therefore be essential reading matter for anyone who has to deal with the new field of nanomaterial technology.